2021
DOI: 10.1155/2021/5511935
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Metastasis of Adenoid Cystic Carcinoma 19 Years after the Primary Tumor Resection

Abstract: Adenoid cystic carcinoma (ACC) is a tumor characterized by slow growth and late distant metastasis. The lung and breast are the most common sites for metastasis. Colonic metastasis of such a tumor is rare, with few case reports available. Here, we report a case of ACC arising from minor salivary gland that metastasized to the colon 19 years after the primary tumor resection, with literature review of the clinical, histological, and molecular features of ACC. This case raises our awareness of such tumors as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although it tends to remain local, late recurrence after treatment is seen. For instance, one case study reported a 78-year-old male who presented with ACC that metastasized to his colon 19 years after the primary tumor was resected [ 4 ]. Due to the wide variability in site of metastasis and time following remission, serial abdominal imaging for recurrence may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Although it tends to remain local, late recurrence after treatment is seen. For instance, one case study reported a 78-year-old male who presented with ACC that metastasized to his colon 19 years after the primary tumor was resected [ 4 ]. Due to the wide variability in site of metastasis and time following remission, serial abdominal imaging for recurrence may be beneficial.…”
Section: Discussionmentioning
confidence: 99%